Facile synthesis of Ge–MWCNT nanocomposite electrodes for high capacity lithium ion batteries. Issue 37 (6th September 2017) - Goriparti, Subrahmanyam; Gulzar, Umair; Miele, Ermanno; Palazon, Francisco; Scarpellini, Alice; Marras, Sergio; Monaco, Simone; Proietti Zaccaria, Remo; Capiglia, Claudio
Abstract : Solvothermal synthesis of Ge–MWCNT. Abstract : Germanium (Ge) nanocrystals combined with multiwalled carbon nanotube (Ge–MWCNT) composites were synthesized via a solvothermal approach and characterized through X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and scanning and transmission electron microscopy (SEM and TEM). The electrochemical behaviour during lithium insertion and de-insertion was investigated by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and galvanostatic charge–discharge measurements. The as prepared Ge–MWCNT nanocomposite exhibits improved cycling performance with higher capacity retention than pristine Ge. The Ge–MWCNTs exhibit a discharge capacity of ∼1160 mA h g −1 after 60 cycles at a current rate of 0.1C. Furthermore, they showed an excellent rate performance at a current rate of 5C (where 1C is 1600 mA g −1 ) by delivering a specific capacity of ∼406 mA h g −1 over 400 charge–discharge cycles.